Electron-beam modification of coating – aluminum substrate systems; IOP Conference Series: Materials Science and Engineering; Vol. 71: International Scientific Conference of Young Scientists: Advanced Materials in Construction and Engineering - Ivanov Yu. F. Yuriy Fedorovich; Krysina O. V. Olga Vasiljevna; Teresov A. D. Anton Dmitrievich; Gracheva M. E. Mariya Evgenjevna (2015, 2015)
Title screen